Sharing semantics among enterprise information systems with contextual ontologies: theory and practice. (2nd April 2007) - Rifaieh, Rami; Benharkat, Aicha Nabila
The Enterprise Information System (EIS) manages enterprise business, applies strategic and economic decisions, and holds communication with partners. Shared semantics are necessary to leverage system engineering benefits such as reusability and interoperability. In the last decade, research on ontologies and contexts was driven separately as formal support for treating the semantics sharing problem. In this paper, we show how to pair-up contexts and ontologies as a formal background for reaching a suitable global enterprise environment. To promote contextual ontologies, we present how to exploit technically the proposed formalism through an architecture and a prototype called Enterprise Information System Contextual Ontologies.